Barriers and Facilitators in Using Personal Hearing Amplifiers from the Perspective of Healthcare Providers - Mansi A. Arora; Janice Xu; Kristina M. Kokorelias; Raphaelle Koerber; Hamsa Krishnapillai; Samir K. Sinha (Canadian Geriatrics Journal, 2026)
Background Hearing loss is experienced by two-thirds of hospitalized older adults and is associated with poor access to healthcare and negative health outcomes. Personal hearing amplifiers (PHAs) are evidence-based assistive devices provided in many hospitals to improve accessibility. However, studies note difficulties in implementing the appropriate use of PHAs. This study seeks to identify barriers and facilitators in using PHAs by healthcare providers in an academic hospital. Methods An ethnographic interview protocol was developed and used to guide voluntary semi-structured interviews with 33 geriatricians, nurses and other allied health professionals, and patient-facing volunteers at Mount Sinai Hospital. The audio interviews were transcribed verbatim and a reflexive thematic analysis was performed. Finally, member checking was completed by sharing results with interviewees who consented to re-contacting and interest-holders within the hospital’s geriatrics program to receive feedback. Results Thematic analysis revealed that regardless of profession, PHAs were perceived as valuable yet underutilized. Under this overarching theme, three key themes were identified around PHA use: barriers to accessibility and availability, lack of designated responsibility, and lack of integration into clinical practice. These findings highlight both the facilitators and barriers associated with implementing PHAs. Discussion PHAs are important accessibility tools, and this study has identified barriers and facilitators to their use by healthcare providers and volunteers communicating with patients with hearing loss. These findings lay the groundwork to test future interventions to promote the increased uptake of PHA devices and greater access to healthcare for older patients experiencing hearing loss.